Study of a fuel cell cogeneration system applied to a brazilian tertiary sector - Silveira, Jose Luz [UNESP]; Leal, Elisângela Martins [UNESP] (ASME International, 2000)
In this paper, a methodology for the study of a molten carbonate fuel cell cogeneration system and applied to a computer center building is developed. This system permits the recovery of waste heat, available between 600°C and 700°C, which can be used to the production of steam, hot and cold water, hot and cold air, depending on the recuperation equipment associated. Initially, some technical information about the most diffusing types of the fuel cell demonstration in the world are presented. In conclusion, the fuel cell cogeneration system may have an excellent opportunity to strengthen the decentralized energy production in the Brazilian tertiary sector.